Innovative solutions in the logistics of tourist services - Nefedova, N.; Prykhodko, Z.; Kolomiyets, K.; Kudelina, S. (Journal of Education, Health and Sport, 2024)
The article is devoted to the study of logistics innovations in the tourism industry. A number of functions performed in the framework of logistics activities by tourism and hospitality enterprises are analyzed. The component structure of tourism lLogistics is considered. The market of digital technologies used in tourism is analyzed.